The effect of fluoxetine and imipramine on the improvement of depressive-like behaviors and HPA axis (hypothalamic-pituitary-adrenal cortex) activity – an animal model - Khaleel, Raghad Abdulsalam; Shareef, Saja Majeed; Hameed, Zinah Essam; Alsaraf, Khulood Majid; Nassar, Maadh Fawzi (ScienceRise: Pharmaceutical Science, 2021)
Depression is one of the most common mental disorders and numerous medications are used to reduce the psychotic symptoms. The aim of this study was to evaluate the therapeutic effects of two commonly used antidepressant drugs, including Fluoxetine (Flx) and Imipramine (IMP) to improve depressive-like behaviors as well as the activity of hypothalamic pituitary-adrenal cortex (HPA). Methods: Initially, 40 adult male albino rats weighing 25±5g were selected for this experimental study. The animals were kept or housed in separate cages under standard temperature (25±1°C) and light-dark conditions (12 hours light/dark cycle). Rats were divided into four groups: each group containing 10 rats, control, immobility stress, Flx receiver, and IMP receiver. Polyethylene restrainer was used to induce immobility stress for 14 days. Finally, the parameters of IMT, ST, serum levels of corticosterone and glucose were evaluated in all four mentioned groups. Results: The results showed that the patient group's immobility time (IMT) increased compared to the control group, but the patient group's swimming time (ST) decreased compared to the control group. The effect of immobility stress on IMT, ST, corticosterone, and glucose factors in the patient group was increasing and decreasing, respectively, whereas the effect of Flx drug on these mentioned factors was decreasing, increasing and respectively, while the effect of IMP on all mentioned factors was decreasing and increasing, respectively. Conclusion: Based on the results, it can be concluded that the antidepressant Flx and IMP drugs have various effects on the HPA activity, and the application of immobility stress causes depressive-behavior. Moreover, Flx is more effective than IMP in the treatment of depressive behaviors